Safety and efficacy of a 6-month home-based exercise program in patients with facioscapulohumeral muscular dystrophy: A randomized controlled trial. Issue 31 (August 2016) - Bankolé, Landry-Cyrille; Millet, Guillaume Y.; Temesi, John; Bachasson, Damien; Ravelojaona, Marion; Wuyam, Bernard; Verges, Samuel; Ponsot, Elodie; Antoine, Jean-Christophe; Kadi, Fawzi; Féasson, Léonard
Abstract: Background: Previous randomized controlled trials investigating exercise training programs in facioscapulohumeral muscular dystrophy (FSHD) patients are scarce and of short duration only. This study assessed the safety and efficacy of a 6-month home-based exercise training program on fitness, muscle, and motor function in FSHD patients. Methods: Sixteen FSHD patients were randomly assigned to training (TG) and control (CG) groups (both n = 8) in a home-based exercise intervention. Training consisted of cycling 3 times weekly for 35 minutes (combination of strength, high-intensity interval, and low-intensity aerobic) at home for 24 weeks. Patients in CG also performed an identical training program (CTG) after 24 weeks. The primary outcome was change in peak oxygen uptake (VO2 peak) measured every 6 weeks. The principal secondary outcomes were maximal quadriceps strength (MVC) and local quadriceps endurance every 12 weeks. Other outcome measures included maximal aerobic power (MAP) and experienced fatigue every 6 weeks, 6-minute walking distance every 12 weeks, and muscle characteristics from vastus lateralis biopsies taken pre- and postintervention. Results: The compliance rate was 91% in TG. Significant improvements with training were observed in the VO2 peak (+19%, P = 0.002) and MAP by week 6 and further to week 24. Muscle endurance, MVC, and 6-minute walking distance increased and experienced fatigue decreased. Muscle fiber cross-sectional area and citrate synthase activity increased by 34% ( P = 0.008) and 46% ( P = 0.003), respectively. Dystrophic pathophysiologic patterns were not exacerbated. Similar improvements were experienced by TG and CTG. Conclusions: A combined strength and interval cycling exercise-training program compatible with patients' daily professional and social activities leads to significant functional benefits without compromising muscle tissue.